2020
DOI: 10.1111/1468-2427.12927
|View full text |Cite
|
Sign up to set email alerts
|

Informal Property Rights as Relational and Functional: Unravelling the Relational Contract in China's Informal Housing Market

Abstract: We thank the IJURR reviewers and the handling editor for their invaluable comments. We are grateful for Pengjun Zhao's great support for our data collection in Beijing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 70 publications
(115 reference statements)
0
13
0
1
Order By: Relevance
“…It is also reported that those dwelling in the dormitory-like housing have a lower ratio of perceiving a fully integrated status (SWB) than those living in informal housing, despite that its regression coefficient is insignificant. Is it reasonable to justify the dispossession by stigmatizing informal housing as a segregated world [ 71 ]? More empirical studies are needed to reveal the relational and functional nature of the so-called “informal” property rights in transitional China.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that those dwelling in the dormitory-like housing have a lower ratio of perceiving a fully integrated status (SWB) than those living in informal housing, despite that its regression coefficient is insignificant. Is it reasonable to justify the dispossession by stigmatizing informal housing as a segregated world [ 71 ]? More empirical studies are needed to reveal the relational and functional nature of the so-called “informal” property rights in transitional China.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit extralegal, above transactional relationships between the village and outside users can get self-enforced by common interests and a reputation system, as analyzed by Zhang and He in 2020 and Qiao in 2017 [34,35]. Informal property rights in destinations provide affordable living and entrepreneurial spaces to millions of rural migrants, creating informal housing markets outside of the formal legal system such as a) petty entrepreneurs and traders from rural Wenzhou congregating in Beijing suburb called Zhejiang Village, and b) small-scale garment factory owners and workers from rural Hubei Province clustering in Guangzhou called Hubei Village [36,37].…”
Section: Rent Dissipation In China's Informal Settlements As Frugal U...mentioning
confidence: 99%
“…Theoretically, this study contributes to a new perspective of understanding the heterogeneous perceived tenure security. Empirically, by unpacking how dwellers develop a perception of the security of their informal tenure, this study deepens the understanding of the formation of SPRH communities, emerging informal settlements that accommodate the disadvantaged lowincome migrant workers and the elderly who are suffering as a result of China's recent housing affordability crisis (He et al, 2019;Zhang and He, 2020a;.…”
Section: Introductionmentioning
confidence: 97%
“…Instead, the state is a contradictory system relatively and unequally open to different actors and thus a site of power struggling amongst different social forces who have their own interests and specific strategies to re-regulate the society (Jessop, 1990). Hence, different state apparatuses may have conflicting interests related to informal settlements and have different and even contradictory strategies to regulate informal tenure (Zhang and He, 2020a). For instance, in China, conflicts of interest related to informal rural land developments exist amongst central authorities (Zhao and Zhang, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation